Predicting Minimal Usage of Plastic Bags Behaviour among Malaysian Adults - Jeffery, Stephen; Abang Muhammad Syaqireen, Abdullah; Izzayul Nazleen, Hussain; Lee, Yee Khay; Shobha Ssri Nair, Makentheran (Academy of Sciences Malaysia, 2024)
Plastic bags consist of synthetic organic polymers that are produced for one-time usage to carry things around. They are lightweight, cheap for mass production and often distributed at no cost in places such as supermarket and shopping malls. There might be numerous factors that affect this increasing usage of plastic bags among the public. The overall objective of this study was to identify factors that influence plastic bag consumption among Malaysians using the Theory of Planned Behaviour. Data were collected by distributing an online questionnaire to the local community. Non-probability purposive sampling method was adopted to select the three states in Malaysia. The path analysis was performed to investigate the relationship between predictor factors (i.e., attitude, subjective norms, perceived behavioural control and intention) and minimal plastic bag usage. A total of 386 people from different ages and backgrounds in Malaysia participated in the research. The findings showed that an individual’s attitude (β = 0.331) and perceived behaviour (β = 0.414) significantly influenced the intention to use plastic bags. The perceived behavioural control (β = 0.329) and intention (β = 0.486) have also significantly influenced the behaviour to minimise plastic bag usage. However, subjective norms did not significantly influence the intention (β = 0.060). This study showed that perceived behavioural control and intention are important predictors towards minimal usage of plastic bags. Therefore, it is recommended to enhance education and awareness programmes among the public in order to change the attitude, perceived behavioural control and intention towards minimal usage of plastic bags. High generation and mismanagement of plastic bag waste, which may lead to a negative impact on environmental health, are the main issues that should be addressed properly by the Malaysian population.